Analisis dan Implementasi Alat Administrasi Jaringan Berbasis Model FCAPS: Studi Efektivitas CMD dan Winbox Pada Lingkungan Mikrotik - Elisa Soleha; Dahliyusmanto; Nanda Dwi Putra; Dimas Panji Eka Jala Putra; Khairul Umam Syaliman (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Riau, 2026)
This study aims to perform an analysis and practical implementation of network administration tools based on the FCAPS model (Fault, Configuration, Accounting, Performance, Security) using Command Prompt (CMD) and WinBox on a simple network consisting of one MikroTik router and one laptop. The research method uses a Systematic Literature Review (SLR) approach and implementative experiments. CMD is used for connectivity testing and network performance, while WinBox is used for IP configuration, firewall management, and traffic monitoring. The results showed that CMD is effective for Fault and Performance Management, while WinBox excels in Configuration and Security Management. Despite limited devices, the application of FCAPS can still be done practically and measurably. This research provides a guide for students and novice network technicians in applying network administration principles simply yet comprehensively.